More synergies or more trade-offs? The interaction among multiple assessment indicators in sustainable urban development in Guangzhou, China. (15th December 2022) - Xie, Yunsheng; Wang, Peng; Yang, Lei; Yang, Muyi; Ren, Songyan; Zhao, Daiqing
Abstract: To achieve sustainable development, local governments are under enormous pressure to simultaneously achieve the three assessment tasks (TATs) of energy saving, CO₂ reduction, and pollution reduction. However, the TATs are often managed by different authorities and have three types of measures (TTMs) that correspond to them. The lack of adequate cooperation between these authorities has led to the inefficient investment of policy resources and even to policy conflicts, and the interactions among the TTMs are not yet known. To this end, this paper uses the MCEE model to assess the interactions among the TTMs quantitatively using Guangzhou, China, as a case study. The results showed the following. (1) According to the current development trend, if the authorities managing the TATs continue to work alone, they will not be able to fulfill the corresponding assessment tasks in the future. (2) The TTMs have interactions with each other, and their synergies are far greater than their trade-offs. From 2015 to 2035, it is expected that energy-saving measures can accomplish 54.39% of the CO₂ reduction tasks and 32.74% of the pollution reduction tasks indirectly, and low-carbon measures can accomplish 55.53% of the energy saving tasks and 27.20% of the pollution reduction tasks indirectly, However, environmental-protection measures will cause fewer trade-offs (energy demand and CO2 emissions increase by 3.76% and 2.88%, respectively). (3) In some years, the contribution of interactions among the TTMs are even higher than their direct contribution to the TATs. Our findings suggest that intensive cooperation between authorities is necessary, and that the benefits of such cooperation will outweigh the disadvantages. Highlights: An integrated energy-economic-environmental assessment model for multiple indicators is established. An index evaluation method for multiple synergies and trade-offs is established. It reveals three types of measures do have interactions and their synergies are far greater than the trade-offs. Intensive cooperation among authorities is necessary and the benefits of such cooperation will outweigh the disadvantages.